Respostas

2014-04-22T13:56:49-03:00
Basta Montar um Sistema =)
Pois isso So vai Acontecer quando o x de uma for igual a da outra e idem para y
Logo,
-2x+y+3=0 y=2x-3 x-y-1=0              |x-y-1=0
x-(2x-3)-1=0      |2 - y - 1 = 0
x-2x+3-1=0        |1-y = 0
-x+2=0               | y =  1
x = 2

P(2,1)


b) Mesma Coisa que a A
3x+y-10= 0                  | y = 10-3x
x+6y+8=0.                   |y = 10 - 3*4
x+6(10-3x)+8=0          |y = 10-12
x+60-18x+8=0            |y = -2
-17x+68=0
17x=68
x = 4

P(4,-2)

3 3 3